Sound & Score: Essays on Sound, Score and Notation - Assis, Paulo de; Brooks, William; Coessens, Kathleen (Leuven Leuven University Press, 2013)
Essays on Sound, Score and NotationExploring the complex and intimate relations between sound, score and notationSound and Score brings together music expertise from prominent international researchers and performers exploring the intimate relations between sound and score and the artistic possibilities that this relationship yields for performers, composers and listeners.Considering notation as the totality of words, signs, and symbols encountered on the road to an accurate and effective performance of music, this book embraces different styles and periods in a comprehensive understanding of the complex relations between invisible sound and mute notation, between aural perception and visual representation, and between the concreteness of sound and the iconic essence of notation.Three main perspectives structure the analysis: a conceptual approach that offers contributions from different fields of enquiry (history, musicology, semiotics), a practical one that takes the skilled body as its point of departure (written by performers), and finally an experimental perspective that challenges state-of-the-art practices, including transdisciplinary approaches in the crossroads to visual arts and dance.ContributorsVirginia Anderson (Experimental Music Catalogue), Paulo de Assis (Orpheus Institute), Sandeep Bhagwati (Concordia University Montréal), Robin T. Bier (University of York), Maria Calissendorff (Royal College of Music, Stockholm), Miguelàngel Clerc (Leiden University), Kathleen Coessens (Vrije Universiteit Brussel and Orpheus Institute), Jeremy Cox (European Association of Conservatoires AEC), Darla Crispin (Orpheus Institute), Anne Douglas (Robert Gordon University), Gregorio García Karman (University of Huddersfield), Yolande Harris (Leiden University), Susanne Jaresand (Royal College of Music, Stockholm), Tanja Orning (Norwegian Academy of Music, Oslo), Paul Roberts (Guildhall School of Music and Drama, London), Anna Scott (Leiden University), Andreas Georg Stascheit (Institute for Advanced Study in the Humanities, Essen/Dortmund University)
Keywords: Music criticism; Notation; Music philosophy and esthetics